Public self-insurance and the Samaritan's dilemma in a federation - Tim Lohse; Julio R. Robledo (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Motivated by recent disasters, this paper analyzes the risk sharing aspect in a federation. The regions can be hit by a shock leading to losses that occur with an exogenous probability and in a stochastically independent way. The regions can spend effort on selfinsurance to reduce the size of the loss. Being part of a federation has two countervailing -elfare effects. On the one hand, there is the well known welfare increase due to risk pooling. On the other hand, the self-insurance effort is a public good, because all regions benefit from the reduction of the loss. There exists a Samaritan's dilemma kind of effect whereby regions reduce their self-insurance effort potentially leading to an overall welfare decrease. The central government can solve this dilemma by committing to fixed rather than variable transfers. This induces regions that behave non-cooperatively to still choose the efficient level of self-insurance effort.
Keywords: H77; H41; H72; 330; intergovernmental transfers; self-insurance; disaster policy; Finanzausgleich; Gefangenendilemma; Katastrophenhilfe; Schock; Selbstversicherung; Theorie